Gambaran Kualitas Resusitasi Jantung Paru dengan Memakai Masker Bedah pada Perawat Rumah Sakit H.A Zaky Djunaid Pekalongan - Mukahar, M; Sulistyanto, Benny Arief (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background: good quality CPR has been proven to increase the patient's survival rate, so that even in the use of masks, nurses must be able to perform CPR with good quality. Objective: This study aims to provide an overview of the quality of CPR using a surgical mask for nurs-es at H.A Zaky Djunaid Hospital Pekalongan. Sample: The sampling technique used the total sampling technique of all nurses at H.A Zaky Djunaid Pekalongan Hospital with a total sample of 59 respondents (Response Rate = 100%). Methods: Data collection tools using Ambu CPR Mannequins and Ambu CPR Software with American Heart Association (AHA) 2020 standards. The stiffness level in the lowest set (Low) or about 6 N/mm (0.6 kg/mm). Respondents were asked to give continuous chest compressions for two minutes while wearing a surgical mask. Results: The results showed that the average compression speed of respondents was 110 x/minute, the average compression depth was 54.95 mm, Hand Position 59 respondents (100%) were in correct hand position, Chest recoil was 59 respondents (100%) correct in chest recoil and Fatigue Level, the results showed that 31 respondents (52.5%) experienced moderate fatigue, 23 respondents (39%) experienced severe fatigue and 5 respondents (8.5%) experienced mild fatigue in cardiac and pulmonary resuscitation by wearing a mask. surgery. Suggestion: Nurses may take turns doing chest compressions if feeling tired (not having to wait the standard two minutes).